Preparation of quadrate crystalline Cu(TCNQ) microtubes and assembly of a novel copatterned structure - Zhou, Xin-Hong (Langmuir : the ACS journal of surfaces and colloids, 2008)
Crystalline microtubes of functional Cu(TCNQ) were prepared using a facile method of dissolution. XRD, SAED, and EDX characterization showed that they belonged to phase I of Cu(TCNQ), which is important in nanoelectronics and nanodevices. Furthermore, a novel micrometer and nanometer structure co-patterned morphology was assembled, which may have potential applicaton in building nanoscale electrodes or patterning other nanosize functional materials